"You think our country's so innocent?" The Trump administration's policy on democratic practices in Russia and the challenge to US identity. Issue 1 (1st January 2020) - Deyermond, Ruth
ABSTRACT: Adopting a constructivist approach to foreign policy analysis, this article considers the Trump administration's policy on democratic practices in Russia, using qualitative discourse analysis. It argues that there has been a retreat from previous administrations' policy, avoiding explicit criticism of the Russian government where possible, and erasing the normative difference between Russia and the US which has been central to US governmental discourse on Russia since the collapse of the Soviet Union. This radical change has implications that extend beyond the bilateral relationship, undermining US identity as constituted through foreign policy by challenging the national narrative that links foreign policy and the concept of American exceptionalism. In particular, the US's identity as the global exemplar and champion of democracy is currently being eroded by the discursive practices of the Trump administration in relation to Russia, threatening the national narrative about the US's normative superiority and exemplary status.